Effects of Globalization on Market Structure, Conduct and Performance in the Nigerian Banking Industry - Akinola, Grace Oluyemisi (2015)
The study assessed the effect of globalization on the structure of Nigerian banks; evaluated the effects on the market conduct; and examined the effect of globalization on product formulation and promotional strategies with a view to appraising the effects of globalization on the performance of Nigerian banks.